Centring stigmatised underserved groups and limiting State competence to counter structural violence:: (Im)permissibility in International Law and South African Law of arrest and detention of undocumented asylum seekers during the asylum application process - Solomons, Nasreen (Department of Public Law, 2024)
South Africa has the competence to regulate the entry and stay of asylum seekers in the country, and to introduce measures of arrest and detention in asylum applications. It enacted the Refugees Act in 1998, which gave effect to its international law obligations in terms of the three specific international and regional refugee law conventions: the 1951 UN Convention Relating to the Status of Refugees, the 1967 UN Protocol relating to the status of refugees and the 1969 OAU Convention governing the specific aspects of refugee problems in Africa. It committed to providing meaningful protection to displaced persons who fled their home countries out of force and need. A key part of this commitment is to provide displaced persons seeking asylum with documentation to regularise their stay in the country. This study is concerned with South Africa's treatment of undocumented asylum seekers. South Africa's commitments in terms of the Act and to its international law obligations have been undone by its current legal framework and practices. Of particular importance is not only the State's failure to protect undocumented asylum seekers from arrest and detention through meaningful assistance during the application process, but also its preference to keep them in a state of being undocumented and therefore vulnerable to arrest and detention. The recent Refugees Amendment Act 11 of 2017 introduced measures that make it easier to arrest and detain undocumented asylum seekers, creating a precarious environment for those most in need of protection during the asylum application process. The study argues that the 2017 amendments (legal framework) and implementation (practices) create an untenable environment for undocumented asylum seekers and amounts to State structural violence. This finding of structural violence can never be permissible in international and constitutional law; therefore, South Africa's competence to introduce measures of arrest and detention in asylum applications must be limited. To respond to the structural violence, any approach formulated and applied must centre the rights and needs of this underserved group and guarantee positive steps are taken to undo structural violence. The study therefore puts forward standards to the limitation of South Africa's competence to regulate arrest and detention in the asylum application process. These standards may form a basis for a new legal and practical framework that centres the rights and needs of undocumented asylum seekers, protects them more substantively, and brings the State into compliance with its international and constitutional obligations.